Integration of Religious Moderation Values in the Administration and Management of Learning in Junior High Schools - Fira Dwiana Nuriska; Sadam Fajar Shodiq (Didaktika: Jurnal Kependidikan, 2026)
Religious moderation is an important value in Islamic education that needs to be continuously internalized through various aspects of educational management in schools. Strengthening the value of moderation does not only depend on the classroom learning process but is also influenced by the administrative system and institutional policies implemented by the school. This study aims to analyze the integration of religious moderation values in school administration and its influence on learning management and students' religious moderation attitudes. This study used a quantitative approach with an exploratory survey design. Data were collected through a Likert-scale questionnaire distributed to 150 eighth-grade students of SMP Muhammadiyah 3 Yogyakarta, selected using a purposive sampling technique. Data were analyzed using Structural Equation Modeling – Partial Least Squares (SEM-PLS) with the help of SmartPLS 4.0 software. The results showed that school administration has a positive and significant influence on learning management. In addition, school administration also has a direct influence on strengthening students' religious moderation attitudes. Other findings indicate that learning management plays a significant role in instilling religious moderation values and mediates the relationship between administrative policies and the formation of students' moderate attitudes. The results of this study confirm that strengthening religious moderation in schools requires synergy between transparent institutional governance and learning practices oriented towards the values of justice, tolerance, and balance.